European and Ukrainian Experience of Anti-Forestalling Regulations - KOROTUN, Volodymyr; BRYDUN, Yevgeniy; NOVYTSKA, Nadiia; KHLIEBNIKOVA, Inna (Journal of Advanced Research in Law and Economics, 2019)
The article is devoted tore search the main trends in the tobacco market in the EU and Ukraine, the dynamics of excise tax revenues. Research methods are as follows: scientific abstraction: generalizations and scientific abstraction; historical and logical; extrapolation; spatial; statistical; graphical and tabular methods of visualization. The purpose and objectives of the study are to assess the effects of increasing the tax burden on excise tax and its impact on the tobacco market in Ukraine, calculate the loss of tax revenue due to excise measures of taxpayers and formulate proposals to combat this phenomenon. The experience of European countries in the field of anti-forestalling regulation is analyzed. It was found that anti-forestalling measures are divided into four types, such as: cap on tax stamps, cap on release for consumption, sell-by date, paying the tax difference. It has been found that in some countries of the EU optimal anti-forestalling regulation has been achieved over a period of time, in several stages and through the introduction of several measures at the same time. Determined that the rapid increase of excise tax rates on tobacco products in Ukraine also caused the problem of forestalling. Estimated that due to this the loss of tax revenues in 2015-2019 to reached 7% of excise tax revenues on tobacco products. It has been proved that current anti-forestalling regulation was not sufficiently effective for counteracting the accumulation of tobacco product stocks. The main results of the study are proposes a new anti-forestalling regulation in Ukraine, by improving the existing measure and introducing an additional term for the circulation of tobacco products in wholesale and retail trade with tax stamps purchased in the previous year to three months.